Advances in Cardiac Electrophysiology and Pacing - Mitacchione, Gianfranco; Curnis, Antonio; Battista Forleo, Giovanni (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Today, interventional treatment and clinical management of cardiac arrhythmias represent a continuous challenge. This is mainly due to the widening of indications for implantable electronic devices and for catheter ablation procedures as well as the continuous improvement of technologies and medical therapies. Despite international guidelines and worldwide consensus updates, evidence gaps persist at all points in the real-world setting. This Special Issue aims to provide a comprehensive overview of advances in the indications, diagnosis, and treatment of cardiac rhythm disturbances, with particular interest in the use of innovative techniques and technologies in interventional therapies.